Exploring the acceptability of a decision aid for rural women with a history of prior cesarean birth regarding subsequent mode of birth in Coatepeque, Guatemala - Jimenez-Zambrano, Andrea; Avery, Morgan; Feller, Kathryn; Rivera, Claudia; Marchin, Angela; Bolaños, Antonio Guillermo; Asturias, Edwin; Rodas, Hector; Harrison, Margo S. (Frontiers in Global Women's Health, 2024)
BackgroundDecisions regarding mode of delivery in the context of a prior cesarean birth is complicated because both trial of labor after cesarean and elective repeat cesarean birth have risks and benefits.PurposeThe objective of this study was to understand the perspective of women and obstetricians in Coatepeque, Guatemala, to guide the development of a decision aid about mode of birth for women with a history of prior cesarean.MethodsWe conducted in-depth semi-structured interviews with obstetricians at Coatepeque Hospital and women at the Center for Human Development in the southwest Trifinio region of Guatemala in February 2020. Using qualitative content analysis, we recorded, transcribed, translated, and analyzed qualitative data for the meaning of themes and concepts exploring the acceptability of counseling with a decision aid regarding mode of delivery.ResultsA total of 30 qualitative interviews were conducted with women and physicians. Three themes emerged from the qualitative interviews: Having a decision aid for women with a prior cesarean birth will be useful and helpful. Content of the decision aid should include benefits and risks for women and babies as well as figures. Women described the need of tailoring the content surrounding family's role in their decisions. They felt that a trusted provider from the healthcare system should facilitate the use of the decision aid for counseling.ConclusionsThese findings emphasize the support and need for innovative approaches to patient education around mode of delivery after a prior cesarean in the southwest region in Guatemala. There is a need to improve the educational information given to women regarding their mode of delivery after a cesarean birth. Finally, an effective decision aid needs to be tailored to not only the women's needs but also the engagement of the family unit for its successful implementation.